Law and Practice of Foreign Arbitration and Enforcement of Foreign Arbitral Awards in Pakistan - Ghouri, Ahmad Ali.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Pakistan has recently reformed its arbitration laws and laws on the recognition and enforcement of foreign arbitration agreements and awards. These reforms relate to both international commercial and investment arbitration. This book highlights the changes brought about by the recent enactments and explains the relationships between the old and new legislation. It provides a detailed and up-to-date analysis of Pakistani case law on foreign arbitration agreements and awards. Part I describes the background of arbitration laws in Pakistan. Part II explains the applicable substantive and procedural rules for the recognition and enforcement of foreign arbitration agreements and awards and other important issues, such as the severability of arbitration clauses from main agreements, questions of public policy, and interim measures supporting foreign arbitration. Part III analyses the recent enactments that implement the New York and the ICSID Conventions in Pakistan.
Introduction -- Analysis of the AA-APC Regime -- The Position of New REFA and AIDA Regimes -- Conclusions.
Keywords: Law; Law; Private International Law, International & Foreign Law, Comparative Law; Dispute Resolution, Mediation, Arbitration; International Economic Law, Trade Law